2018
DOI: 10.1039/c8en00054a
|View full text |Cite
|
Sign up to set email alerts
|

Aging reduces the toxicity of pristine but not sulphidised silver nanoparticles to soil bacteria

Abstract: Aging of silver nanoparticles shows soluble silver driving toxicity in ISO medium, but not in media containing natural organic matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 52 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…For example, silver NPs released into sewage change to Ag 2 S, which is less toxic than pristine silver NP. [ 138 ] Organic matter, especially HA and fulvic acid, attach to the NP surface and reduce its toxicity against soil bacteria.…”
Section: Np Impacts On Bacterial Community In the Environmentmentioning
confidence: 99%
“…For example, silver NPs released into sewage change to Ag 2 S, which is less toxic than pristine silver NP. [ 138 ] Organic matter, especially HA and fulvic acid, attach to the NP surface and reduce its toxicity against soil bacteria.…”
Section: Np Impacts On Bacterial Community In the Environmentmentioning
confidence: 99%
“…In the category of metal oxides, Pulido-Reyes et al showed that cerium oxide NPs coated with polyvinylpyrrolidone (PVP) significantly increased the formation of reactive oxygen species in exposed cells, indicating that oxidative stress is an important toxicity mechanism for NPs (Pulido-Reyes et al, 2019). Additionally, Schultz et al observed a similar behavior between nZVI and silver-based nanoparticles: aging transformations reduced the bactericidal effect of pristine and sulfidized nano-Ag in media with organic matter, although the release of cationic silver through dissolution could not account entirely for the observed toxicity (Schultz et al, 2018).…”
Section: Other Type Of Nanoparticlesmentioning
confidence: 99%
“…A decrease in soil pH has been shown to increase toxicity or bioaccumulation of Ag, ZnO, TiO 2 nanoparticles to Eisenia fetida , C. elegans , soil microbial community composition, and carbon mineralization. [ 76–80 ] The ionic strength of exposure media also plays a role in NM uptake and toxicity. It was found to be positively correlated with increased Ag NM aggregation and dissolution which promoted toxicity to Escherichia coli , [ 81 ] however, the opposite was the case for TiO 2 where only aggregation was increased.…”
Section: Assessing How Transformations Impact On Bioaccumulation and mentioning
confidence: 99%
“…For example, a 24 h aging step in ISO medium in the presence of fulvic acid significantly decreased growth inhibition by Ag NMs in bacteria. [ 77 ] The observed decrease in toxicity was linked to passivation of the NM surfaces by the organic matter, since no differences in dissolution were found. Studies with D. magna have also included such an incubation step as a presaging reaction before toxicity testing.…”
Section: Assessing How Transformations Impact On Bioaccumulation and mentioning
confidence: 99%